Nikah Mutâ€™ah dalam Perspektif Al-Qurâ€™an dan Hadis - Siregar, Khairil Ikhsan (Jurnal Studi Al-Qur’an, 2012)
The research on verse 24 of the letter an-Nisa ’ and hadis apostles about mut’ah marriage (contract marriage) has received the attention of the Sunni scholars as the study of exegesis and sharh hadith of the Prophet which stipulates that mut’ah marriage is illegitimate. It is a benchmark for the opinion of the Syiâ€™ah who claimed that mut’ah marriage (contract marriage) is kosher. Syiâ€™ah also accused some Sunni scholars have done foolishness by reading books of tafsir and hadith sharh Sunnis to deceive the public. Keywords : Mut’ah Marriage, an-Nisa ’ 24